2007
DOI: 10.1007/s11060-007-9349-8
|View full text |Cite
|
Sign up to set email alerts
|

The anti-cancer compound Nordy inhibits CXCR4-mediated production of IL-8 and VEGF by malignant human glioma cells

Abstract: The chemokine receptor CXCR4 plays an important role in tumor growth, angiogenesis and metastasis. Our previous studies showed that Nordy, a synthetic chiral compound of nordihydroguaiaretic acid, inhibited the growth and angiogenesis of various malignant tumors. In this study we examined the capacity of Nordy to regulate CXCR4-mediated production of angiogenic factors by human glioblastoma cells. We found that Nordy potently inhibited CXCR4 ligand SDF-1-induced production of IL-8 and vascular endothelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…In addition, the inhibition of the CXCL12/CXCR4 axis generates impairment of tumor-producing angiogenic factors, such as interleukin-8 and VEGF, resulting in the failure of tumor angiogenesis [58,59]. CXCL12 expression is crucial for tumor development associated with the tumor cell survival and tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the inhibition of the CXCL12/CXCR4 axis generates impairment of tumor-producing angiogenic factors, such as interleukin-8 and VEGF, resulting in the failure of tumor angiogenesis [58,59]. CXCL12 expression is crucial for tumor development associated with the tumor cell survival and tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Brand and colleagues have demonstrated that ASC-derived SDF-1 stimulation induces a significant increase in proangiogenic factors such as VEGF protein levels [32]. Furthermore, it has been reported that SDF-1 may contribute to the production of other angiogenic factors such as IL-8 and MMP-3 by tumor cells through both receptors, CXCR4 and CXCR7 [4,8].…”
Section: Discussionmentioning
confidence: 99%
“…They succeeded to inhibit the breast cancer metastasis using a CXCR4 neutralizing antibody [7]. Moreover, CXCR4 may contribute to the production of angiogenic factors such as interleukin-8 (IL-8) and vascular endothelial growth factor (VEGF) by tumor cells [8]. Through angiogenesis, regulated upon activation, normal T cell expressed and secreted (RANTES) and monocyte chemotactic protein (MCP)-1 has also been reported to have tumor promoting effects [9].…”
Section: Introductionmentioning
confidence: 99%
“…For RT-PCR to detect SDF-1, VEGF and CXCR4 mRNA expression, 1 μg of total RNA from U87 cells treated with different factors was subjected to RT-PCR using two-step RT-PCR kit according to the protocol described by the supplier. Each PCR reaction and the PCR products analyses were performed as described in [14]. The primer pairs were as follows: β-actin …”
Section: Reverse Transcription-polymerase Chain Reaction (Rt-pcr)mentioning
confidence: 99%